2018
DOI: 10.1177/1120672118805875
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tunnel length and position on postoperative corneal astigmatism: An optical coherence tomographic study

Abstract: Purpose: The purpose of this study is to evaluate the effects of variation in tunnel length of same-sized clear corneal phacoemulsification incisions on the generation of surgically induced astigmatism and corneal astigmatism. Methods: A total of 126 cataract patients treated in four study groups based on location and tunnel length of the clear corneal incisions (superior long, superior short, temporal long, temporal short) were reviewed. In the short tunnel groups, a 2.8 mm keratome was used with a motion par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Choi et al's work standardized the CCI deformities by wound deformity scoring and found positive correlations between SIA and wound instability (Choi et al 2016). Our results were in agreement with the previous studies (Wilczynski et al 2016;Sonmez & Karaca 2020;Hayashi et al 2018b), and we further evaluated the correlation between the CCI features and corneal SIA on the anterior and posterior surfaces at 1 and 6 months postoperatively.…”
Section: Sia and CCI Featuressupporting
confidence: 91%
“…Choi et al's work standardized the CCI deformities by wound deformity scoring and found positive correlations between SIA and wound instability (Choi et al 2016). Our results were in agreement with the previous studies (Wilczynski et al 2016;Sonmez & Karaca 2020;Hayashi et al 2018b), and we further evaluated the correlation between the CCI features and corneal SIA on the anterior and posterior surfaces at 1 and 6 months postoperatively.…”
Section: Sia and CCI Featuressupporting
confidence: 91%
“… 22 , 23 Sonmez et al examined the additional effect of tunnel length on different incision sites and found that a shorter tunnel may be beneficial for a superior CCI to limit the SIA. 24 Apart from that, wound stretching was suggested to be a contributing factor. 12 Vasavada et al compared corneal incision enlargement and SIA using CCIs of 1.8 mm and 2.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the position of the incision, there are corneal, limbal, scleral, and corneoscleral incisions. The most frequently used approach in modern cataract surgery is a corneal incision, and the postoperative astigmatism is smaller with increasing distance from the cornea [ 3 , 4 ]. Most studies suggest that the temporal position of the incision results in smaller surgically induced astigmatism if there is mild preoperative astigmatism and against-the-rule astigmatism [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%